Al-Qur'Än Interpretation Pattern by Adi Hidayat on Adi Hidayat Official YouTube Channel - Suryadinata, M.; Wahid, Abdul; Ernawati, Ernawati; Arib, Juhrah M.; Putra, Sudarmadi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
This study aims to analyze Adi Hidayat's al-Qur'Än interpretation on an official YouTube channel. It ensures that the public is not exposed to inferior information as the use of new media to interpret the al-Qur'Än in the digital age increases and regulation becomes more complex.Â Therefore, new problems in the al-Qur'Än interpretation are inevitable. Becoming a mufassÄ«r necessitates expertise, and the al-Qur'Än interpretation should adhere to the same rules. A qualitative and virtual ethnographic approach was used to analyze the data. Primary data was obtained from Adi Hidayat's video interpretation of sÅ«rah an-NÅ«r, sÅ«rah YusÅ«f, and tafsÄ«r on the Jewish genealogy history, as well as studies on Islamic questions and answers. Similarly, books and journals were used as secondary data and analyzed using qualitative analysis techniques. The results showed that Adi Hidayat's interpretation style was lugÄwÄ« and tended to use the mauá¸Å«'i than the tahlÄ«lÄ« method with the bil ma'sÅ«r and bil ra'yi approaches. Additionally, the tafsÄ«r book was not the only source of interpretation and tends to rely on personal ijtihÄd through language analysis, as well as reviewing the wisdom of a verse rather than explaining the global meaning. This study contributes to the discovery of the al-Qur'Än interpretation aspects by Adi Hidayat. It shows the importance of social media as an essential tool for mufassÄ«r because of its easy accessibility for the public.